Dependence of spin-orbit torque effective fields on magnetization uniformity in Ta/Co/Pt structure - Luo, Feilong (2019)
The spin-orbit torque (SOT) effective fields, namely field-like and damping-like terms, depend on the thicknesses of heavy metal (HM) and ferromagnetic metal (FM) layers, in a stack comprising of HM/FM/HM or oxide. In this work, we report on the dependence of the SOT effective fields on the magnetization uniformity in the wires comprising of Ta/Co/Pt layer structure. SOT dependence on magnetization uniformity dependence was investigated by concurrent variation of the magnetization uniformity in Co layer and characterization of the SOT effective fields in each wire which excludes the layer thickness dependence influences. Our experimental results reveal that the field-like term decreases while the damping-like term increases with increasing Co magnetization uniformity. The magnetization uniformity influence on the effective fields is attributed to the spin Hall effect, which contributes to the SOT.